(untitled) (Scottish Archaeological Internet Reports, 2009)
The aim of the survey work was to examine the coastline of the Inner Sound for evidence of past human activity. As the focus was primarily on the Mesolithic, upstanding sites that were obviously of a later date, such as cairns, hut circles, shielings and so on were excluded.